Hijratun Nabi: Teladan inspiratif hijrahnya Rasulluah dari Mekkah Ke Madinah - Vidhania, Aiska Rahma (Maliki Interdisciplinary Journal, 2024)
Hijrah, in terminology, refers to a process of transitioning oneself to become a better person by leaving behind everything that is forbidden by Allah. This is exemplified by the migration of Prophet Muhammad (PBUH) and his followers from the city of Mecca to Yathrib, which later became the city of Medina, in 622 AD, thirteen years after Prophet Muhammad was sent as Allah's Messenger. This event was triggered by the dissatisfaction of the Quraysh tribe in Mecca with Prophet Muhammad's call, which urged people to abandon idol worship and turn to the worship of Allah SWT, adhering to monotheism as a continuation of the tradition of Tawhid that had been taught by previous prophets, starting from Prophet Adam AS to Prophet Jesus AS. Prophet Muhammad's efforts to uphold the principle of monotheism were opposed by the majority of the Quraysh community, who were idol worshippers. Despite facing various forms of rejection and threats, including slander, insults, physical attacks, economic barriers, and assassination plots, Prophet Muhammad remained patient and never cursed the people of Mecca.